On the Hadamard Well-Posedness of Generalized Mixed Variational Inequalities in Banach Spaces - Lu-Chuan Ceng; Yeong-Cheng Liou; Ching-Feng Wen; Hui-Ying Hu; Long He; Yun-Ling Cui (Journal of Mathematics)
We introduce a new concept of Hadamard well-posedness of a generalized mixed variational inequality in a Banach space. The relations between the Levitin–Polyak well-posedness and Hadamard well-posedness for a generalized mixed variational inequality are studied. The characterizations of Hadamard well-posedness for a generalized mixed variational inequality are established.